Does Health Affect Party Identification? Evidence from German Panel Data. Issue 2 (3rd April 2019) - Papageorgiou, Achillefs; Mattila, Mikko; Rapeli, Lauri
ABSTRACT: Recent research has shown the effect of health on voter turnout, arguing that attenuated health depresses voting. However, we know little about how health is connected to the psychological factors, such as party identification, that precede actual political participation. Employing data from the German Socio-Economic Panel (SOEP), we show that when a person's health deteriorates, the degree of partisan attachment declines, whereas health improvement does not automatically restore the level of party identification to previous levels.